Epiphytic Diatoms along Environmental Gradients in Western European Shallow Lakes. Issue 3 (29th August 2013) - Blanco, Saúl; Cejudo‐Figueiras, Cristina; Álvarez‐Blanco, Irene; van Donk, Ellen; Gross, Elisabeth M.; Hansson, Lars‐Anders; Irvine, Kenneth; Jeppesen, Erik; Kairesalo, Timo; Moss, Brian; Nõges, Tiina; Bécares, Eloy
<x xml:space="preserve">Abstract</x> Diatom‐based assays have been successfully associated worldwide with the tropic status of lakes. Several studies have demonstrated a correlation between epiphytic diatoms and nutrient load in shallow lakes and wetlands. We examine the relative importance of environmental factors in explaining the structure of epiphytic diatom communities in a set of Western European shallow lakes. The effects of lake physical/chemical, morphometric, and geographical variables on diatom assemblages were tested using distance‐based, canonical correspondence and regression analyses. Our results show that epiphytic diatom communities respond, mainly to physical/chemical variables, overriding the effects of lake depth, size, and location. The clustering of studied systems based along a total phosphorus concentration gradient concurs with previous classification of diatom taxa and nutrient state. Assessment of epiphytic diatoms provided a potential method for shallow lake classification.